The Ti plasmid increases the efficiency of Agrobacterium tumefaciens as a recipient in virB-mediated conjugal transfer of an IncQ plasmid - Bohne, Jutta (The National Academy of Sciences, 1998)
The T-DNA transfer apparatus of Agrobacterium tumefaciens mediates the delivery of the T-DNA into plant cells, the transfer of the IncQ plasmid RSF1010 into plant cells, and the conjugal transfer of RSF1010 between Agrobacteria. We show in this report that the Agrobacterium-to-Agrobacterium conjugal transfer efficiencies of RSF1010 increase dramatically if the recipient strain, as well as the donor strain, carries a wild-type Ti plasmid and is capable of vir gene expression. Investigation of possible mechanisms that could account for this increased efficiency revealed that the VirB proteins encoded by the Ti plasmid were required. Although, with the exception of VirB1, all of the proteins that form the putative T-DNA transfer apparatus (VirB1–11, VirD4) are required for an Agrobacterium strain to serve as an RSF1010 donor, expression of only a subset of these proteins is required for the increase in conjugal transfer mediated by the recipient. Specifically, VirB5, 6, 11, and VirD4 are essential donor components but are dispensable for the increased recipient capacity. Defined point mutations in virB9 affected donor and recipient capacities to the same relative extent, suggesting that similar functions of VirB9 are important in both of these contexts.